2021
DOI: 10.3390/molecules26030560
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Chitosan-Coated Rhamnolipid Liposomes Containing Curcumin: Stability and In Vitro Digestion

Abstract: There is growing interest in developing biomaterial-coated liposome delivery systems to improve the stability and bioavailability of curcumin, which is a hydrophobic nutraceutical claimed to have several health benefits. The curcumin-loaded rhamnolipid liposomes (Cur-RL-Lips) were fabricated from rhamnolipid and phospholipids, and then chitosan (CS) covered the surface of Cur-RL-Lips by electrostatic interaction to form CS-coated Cur-RL-Lips. The influence of CS concentration on the physical stability and dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…For instance, at pH 7.4, the drug release rate was significantly higher in uncoated than coated liposomes (Karim et al, 2021). CS coating can prevent rapid drug release due to gastric acid degradation (Sağıroğlu, 2021; Zhou et al, 2021). HA‐modified liposomes can also delay initial drug efflux and improve drug release in highly acidic conditions (Park et al, 2014).…”
Section: Characteristics Of Polysaccharide‐coated Liposomal Drug Deli...mentioning
confidence: 99%
“…For instance, at pH 7.4, the drug release rate was significantly higher in uncoated than coated liposomes (Karim et al, 2021). CS coating can prevent rapid drug release due to gastric acid degradation (Sağıroğlu, 2021; Zhou et al, 2021). HA‐modified liposomes can also delay initial drug efflux and improve drug release in highly acidic conditions (Park et al, 2014).…”
Section: Characteristics Of Polysaccharide‐coated Liposomal Drug Deli...mentioning
confidence: 99%
“…Furthermore, liposomes containing both the compounds lysozyme and nisin showed higher stability and antimicrobial activity compared to liposomes containing lysozyme, representing a promising co-delivery system for bioactive substances [ 148 ]. Water-soluble vitamin E derivative of PEG, d--tocopheryl polyethylene glycol 1000 succinate (TPGS).…”
Section: Nanotechnology As a Nutraceutical Properties Enhancement Str...mentioning
confidence: 99%
“…However, liposomes are thermodynamically unstable and prone to aggregation and oxidation during storage, leading to the leakage of encapsulating materials (Chen et al ., 2020; Pownall et al ., 2021). Some polysaccharides have been introduced as coatings attached on the liposome surface to improve the structural stability of the liposome system, such as chitosan, sodium alginate or their combination (Mengdan et al ., 2020; Carine et al ., 2021; Zhou et al ., 2021). A study on chitosan coating showed that chitosan‐coated liposomes improved the antioxidant activity and stability of eugenol when compared with regular liposomes (Sebaaly et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%